The Redefinition of the Mole — the Background of Changes in the International System of Units and Their Impact on Education - Schubertová, Romana; Held, Ľubomír (Scientia in educatione, 2015)
This article connects an ongoing discussion about the redefinition of basic units in the International System of Units with the teaching of chemistry. The “new” definition of mole is to be based on the precise determining of Avogadro constant. However, problems related to this new definition have roots in the history of the quantity amount of substance itself. One of the main problems is the fact that the amount of substance is the only discontinuous quantity (from among basic quantities) whose unit ‘mole’ was not introduced in the International System of Units on the basis of properties of the nature, but only by human agreement. Thus, the question is whether the mole is correctly placed among basic units of the International System of Units. This is one of the reason why this quantity is also interesting from the didactic point of view. It is discussed in this article.